KOORDINASI PENYELENGGARAAN PROGRAM REHABILITASI SOSIAL RUMAH TIDAK LAYAK HUNI DI KECAMATAN CICURUG KABUPATEN SUKABUMI - Dhara Nur Annisa E; Herijanto Bekti; Sawitri Budi Utami (Universitas Padjadjaran, 2022)
Social welfare problems marked by the condition of uninhabitable houses are still being felt in Cicurug District, Sukabumi Regency, the Sukabumi Regency government then takes care of these problems through the Uninhabitable House Social Rehabilitation Program (RS-RTLH). This study aims to analyze the coordination of the implementation of the Social Rehabilitation Program for Uninhabitable Houses (RS-RTLH) in Sukabumi Regency, especially in Cicurug District. The theoretical basis used as material for analysis is the coordination theory proposed by Bose (2012) which consists of six techniques that help achieve effective coordination, namely Clearly defined goals, Clear lines of authority and responsibility, Precise and comprehensive programs and policies, Cooperation , Effective communication, and Effective leadership and supervision. The research method used is a qualitative research method. Data collection techniques used by researchers by way of observation, interviews, documentation. Furthermore, the data processing techniques used by researchers in this study used data descriptions, theme analysis and highlighting. The results of the study showed that the six techniques proposed by Bose (2012) as an analytical knife for the Coordination of the Implementation of the RS-RTLH Program in Cicurug District, Sukabumi Regency in 2019 showed that coordination had not been effective. This can happen because cooperation has not been achieved, the form of cooperation carried out through community self-help has not been fully realized in the village in Cicurug District and awareness of a sense of mutual help that is less developed in the community around the recipients of social assistance, and not achieving effective leadership and supervision. the implementation of a regional leadership system but the lack of active leaders at the village level and the absence of technical facilitators/technical assistance teams as a form of supervision in the field, resulting in order and provision of program implementation reports that are not in accordance with the implementation rules of the RS-RTLH in Cicurug District in 2019. Masalah kesejahteraan sosial dengan ditandai kondisi rumah tidak layak huni masih tengah dirasakan di Kecamatan Cicurug Kabupaten Sukabumi, pemerintah Kabupaten Sukabumi kemudian melakukan penanganan terhadap permasalahan tersebut melalui Program Rehabilitasi Sosial Rumah Tidak Layak Huni (RS-RTLH). Penelitian ini bertujuan untuk menganalisis koordinasi dari penyelenggaraan program Rehabilitasi Sosial Rumah Tidak Layak Huni (RS-RTLH) di Kabupaten Sukabumi khususnya pada Kecamatan Cicurug. Dasar teori yang digunakan sebagai bahan analisis adalah teori koordinasi yang di kemukakan oleh Bose (2012) yang terdiri dari enam teknik yang membantu mencapai koordinasi yang efektif, yaitu Clearly defined goals, Clear lines of authority and responsibility, Precise and comprehensive programmes and policies, Cooperation, Effective communication, and Effective leadership and supervision. Metode penelitian yang digunakan adalah metode penelitian kualitatif. Teknik pengumpulan data yang digunakan oleh peneliti dengan cara observasi, wawancara, dokumentasi. Selanjutnya teknik pengolahan data yang digunakan peneliti dalam penelitian ini menggunakan deskripsi data, analisis tema dan penonjolan. Hasil penelitian yang diperoleh bahwa enam teknik yang dikemukakan oleh Bose (2012) sebagai pisau analisis Koordinasi Penyelenggaraan Program RS-RTLH di Kecamatan Cicurug Kabupaten Sukabumi Tahun 2019 menunjukan koordinasi yang belum efektif. Hal tersebut dapat terjadi karena belum tercapainya kerjasama, bentuk kerjasama yang dilaksanakan melalui swadaya masyarakat belum terealisasi keseluruhan di desa di Kecamatan Cicurug serta kesadaran akan rasa saling membantu yang kurang terbangun di lingkup masyarakat sekitar penerima bantuan sosial, dan tidak tercapainya kepemimpinan dan pengawasan yang efektif, diterapkannya sistem kepemimpinan secara kewilayahan namun kurang aktifnya pemimpin di tingkat desa serta tidak adanya fasilitator teknis/tim pendamping teknis sebagai bentuk pengawasan di lapangan sehingga mengakibatkan ketertiban dan ketetapan laporan pelaksanaan program kurang sesuai dengan aturan pelaksanaan RS-RTLH di Kecamatan Cicurug tahun 2019.